Synthesis and Antiinflammatory Activity of 2-[5’-(4-Pyridinyl)-1’,2’,3’-oxadiazol-2-ylthiomethyl]- 3-substituted-aryl-6-substituted-quinazolin-4-ones - Singh Rajput, Chatrasal; Kumar, Ashok; Kumar Bhati, Sudhir; Singh, Jai (Asian Journal of Chemistry, 2010)
In present study, a novel series of quinazolin-4-ones derivatives viz., 2-methyl-3-substituted aryl-6-substituted quinazolin-4-ones (4-18), 2-bromomethyl-3-substitutedaryl-6-substuted quinazolin- 4-ones (19-33), 2-[5'-(4-pyridinyl)-1',3',4'-oxadiazol-2'-yl-thiomethyl]- 3-substituted aryl-6-substituted quinazolin-4-ones (34-48) have been synthesized. The structures of all these newly synthesized compounds were confirmed by their analytical and spectral data. The compounds were evaluated for their antiinflammatory activity. Compound 43 showed maximum antiinflammatory (36.25 %) activity at the dose of 50 mg/kg p.o.